Selected Cases of Corporal Punishment Experiences in Malaysian Schools - Visvalingam, G. Perumal (2016)
At the time of writing the media had been rife with the story of a ‘moral’ education teacher throwing a shoe at a female pupil. The shoe had cut the chin of the child and the wound needed three sutures and medical care, (The Star, 12 July 2014, p. 26).The physical wound suffered by the child will heal in time. What is uncertain is how long more school children have to endure punishment and verbal abuse at school. What feelings do students experience when he/ she is punished? This study is unique for it is a study about the practice of corporal punishment from the ‘outside’, with phenomenology as the methodology. Malaysian students, although, now a few years removed from the school setting, were interviewed to obtain rich data recorded electronically. The use of interviews to elicit data was an epistemological preference. The objective was to gain insight into the deep feelings of the victims. This study is therefore an investigation of the first person account of nine interview respondents, chosen on a ‘purposive’ basis. The objective was to decipher their feelings in order to explore the nuances and examine the constituents of this experience, how it had affected the children at that point of time, and how it affects them presently. Literature and research work on the topic was reviewed in order to link the respondent’s views, their recollections and experiences with corporal punishment. The data collected was transcribed and interpolated to reveal deep- set feelings harboured by the punished. The study revealed some unexpected results which are elaborated scholastically; avenues for further research are advanced and the recommendations should to spur deep considerations, scholastic discussions and lots of soul searching among all stakeholders.